Use of smart edible topping based on whey and jaboticaba rind extract in cheese plate (Research, Society and Development, 2020)
The objective was to develop an edible coating, in the form of cylindrical ribbons, to be added in packages of Prato cheeses, using constant concentrations of whey and increasing extracts of jaboticaba peel. For this, anthocyanic compounds present in the bark of the fruit were extracted in cold solution. Subsequently, three different concentrations of this extract were transferred to the filmogenic solutions containing whey, cassava starch and glycerol. For greenhouse drying, the solutions were placed in Petry Acrylic plates and waited within 32 hours. After this process, the edible coatings were applied in Prato cheese and analyzed in five time intervals: 0, 15, 30, 45 and 60 days. During this period, changes in color and pH patterns were observed. The active and intelligent edible coatings modified the color along with the pH change from the first 15 days of analysis. This change gave the coating bioactivity.